Cahaya Enterprise : Lamp Installment Services / Ahmad Akmal Azman ...[et al.] - Azman, Ahmad Akmal; Roseade, Nur Khairunisa; Hamdan, Faiz Izzat; Sahruazman, Mohamad Sahrulidzuan; Abd Rahim, Ahmad Irfan (2017)
Our product are use to control light by using light dependent resistant (LOR) and timer. The LDR will operate when the light intensity is low. While, the timer is set by the user themselves whenever they want the lamp to light up. Our product and service are suitable for houses, factory and office.